The 13th juror : a novel - Lescroart, John T. (New York : Island Books, 1995)
A legal thriller featuring a battered San Francisco wife accused of shooting both her husband and her seven-year-old son. When the trial opens she refuses to allow a defense of spousal abuse because of its implication of guilt. Which presents her lawyer, the narrator, with a major problem as the prosecution claims she killed the husband for the insurance.
National College of Business and Arts
Keywords: Murder -- Fiction; Detective and mystery fiction